ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN AUGMENTED REALITY BERBASIS ANDROID DI SMA NEGERI 1 SUNGAI KUNYIT - Iqbal, Muhammad; Koriaty, Sri; Nurbani; Fatmawati, Erni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The objective of this study is to conduct a needs analysis for the development of Android-based Augmented Reality learning media at SMA Negeri 1 Sungai Kunyit. This research employs a qualitative approach. The population includes all teachers and students involved in the Informatics learning process at SMA Negeri 1 Sungai Kunyit. The sample was selected using purposive sampling, consisting of two Informatics subject teachers and two students from SMA Negeri 1 Sungai Kunyit. Data were collected through interviews, observations, and questionnaires. The analysis results indicate that Informatics learning at SMA Negeri 1 Sungai Kunyit faces challenges due to limited facilities, such as computer laboratories and textbooks. Therefore, Android-based Augmented Reality learning media is needed to support a more interactive and innovative learning experience.